Answer to Question #13983 in Real Analysis for Nevetha
2012-08-31T07:21:56-04:00
using principle of mathamatical induction prove that a+(a+d)+(a+2d)+...........+[a+(n-1)d] =
n/2[2a+(n-1)d]
1
2012-09-04T10:46:13-0400
Let n=1 Then a+(a+d)+(a+2d)+ ... +[a+(n-1)d] = a On the other hand, n/2[2a+(n-1)d] = 1/2 * 2a = a So these expresions coincide. Supose that we have proved the identity for all k<n+1, so in particular, for k=n we have that a+(a+d)+(a+2d)+ ... +[a+(n-1)d] = n/2[2a+(n-1)d] We have to prove the identity for k=n+1, that is a+(a+d)+(a+2d)+ ... +[a+(n-1)d] + [a+nd] = (n+1)/2 * [2a+nd] Notice that by induction a+(a+d)+(a+2d)+ ... +[a+(n-1)d] + [a+nd] = n/2[2a+(n-1)d] + [a+nd] = na + n(n-1) d/2 + a + nd = (n+1) a + (n^2/2 - n/2 + n) d = (n+1) a + (n^2/2 + n/2) d = (n+1) a + (n+1) n d /2 = (n+1)/2 [ 2 a + n d ]
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS !
Comments
Leave a comment